Effect of Carbon Nanotubes on Liquid Crystal Behavior in Electric and Magnetic Fields Studied by SAW. (2017) - Veveričík, Marek; Bury, Peter; Kopčanský, Peter; Timko, Milan; Mitróová, Zuzana
Abstract: The effect of multi-walled carbon nanotubes (MWCNT) and functionalized MWCNT (MWCNT/Fe3 O4 ) on structural changes in thermotropic liquid crystal (6CHBT) was studied using the attenuation measurement of surface acoustic wave (SAW) propagating along the liquid crystal. Both kinds of nanoparticles of low volume concentration (1 × 10 –4 ) were added to the liquid crystal during its isotropic phase. Pure 6CHBT liquid crystal was used for the comparison of structural changes and orientational coupling of the liquid crystals molecules with both types of carbon nanotubes. These observations proved, that the doping process significantly affected the behavior of liquid crystal in applied electric and magnetic fields, and indicated potential application.